Minority vs. majority: An experimental study of standardized bids - Agnes Pintér; Robert F. Veszteg (Osaka University, Institute of Social and Economic Research (ISER), 2008)
Due to its simplicity the plurality voting system is frequently used to choose a common representative or project. Nevertheless it may fail to provide a socially efficient decision as a majority can outvote any minority even if the majority's gain does not compensate the loss suffered by the minority. In this paper we propose and study a simple mechanism that allows voters to reveal more information about their preferences over the candidates. According to the standardized bids mechanism voters report a bid for all the available projects. Standardization ensures the existence of equilibrium, and delivers incentives to overcome the problem of positive and negative exaggeration. Our experimental results show that the standardized bids mechanism performed well in the laboratory as it chose the efficient project in almost three quarters of the cases, and induced truthful reports of project rankings in approximately 90% of the cases. For a reference, we also present experimental results for the plurality voting scheme.
Keywords: C92; D71; D82; 330; efficiency; experiments; mechanism design; public project; uncertainty; voting rules